PENGARUH RETURN ON ASSETS (ROA) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PT. UNILEVER INDONESIA TBK PERIODE 2010-2023 - Silvina Nur Annisa; Maswarni (Journal of Research and Publication Innovation, 2024)
This research aims to determine how much influence Return On Assets (ROA) and Debt to Equity Ratio (DER) both partially and simultaneously have on share prices at PT Unilever Indonesia Tbk during the 2010-2023 period. The research method used in this research is a descriptive quantitative method. The population used is all annual financial reports of PT Unilever Indonesia Tbk. The sample used in this research is a financial position report (balance sheet), profit and loss report, and stock overview at PT. Unilever Indonesia Tbk during the 2010-2023 period. The data analysis method in this research uses the classical assumption test, simple linear regression test, multiple linear regression test, correlation coefficient test, coefficient of determination test (R²) and hypothesis testing using the SPSS version 26 approach. The results of hypothesis testing using the T test show that The partial Return On Assets (ROA) variable has a significant effect on share prices with a value of tcount > ttable (2.301 > 2.201) and has a significance value of 0.042 < 0.05. Meanwhile, Debt to Equity Ratio (DER) partially has no significant effect on share prices with a value of tcount > ttable (1.120 < 2.201) and has a significance value of 0.287 > 0.05. The results of hypothesis testing using the F Test show that simultaneously Return On Assets (ROA) and Debt to Equity Ratio (DER) have a significant effect on share prices with an F value of 4.600 with a significance level of 0.035. This shows Fcount > Ftable (4,600 > 3.98) with a significance value of 0.035 < 0.05.